LENGTH- WEIGHT AND TAIL LENGTH -TOTAL LENGTH RELATIONSHIP IN PANULIRUS HOMARUS LINNAEUS OF THE SOUTH -WEST COAST OF INDIA - MEENAKUMARI, B; RAJAN, K. V MOHAN; NAIR, A.K KESAVAN (Fishery Technology, 2017)
Length-weight relationships of Panulirus homarus caught from the Kanniyakumari coast was found to be W = 0.000566 L 2 . 5Â°. The relationship between tail length and total length was also investigated and compared with that of Panulirus polyphagus. Same relationship did not hold good for the two sexes as in the case of P. polyphagus. For a given tail length, the head length, the total length and the weight appear to berelatively larger for females of small sizes of P. homarus.